The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1371/journal.pone.0024879
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Dendritically Localized mRNA Neuronatin in Hippocampal Neurons

Abstract: Local translation of dendritic mRNAs plays an important role in neuronal development and synaptic plasticity. Although several hundred putative dendritic transcripts have been identified in the hippocampus, relatively few have been verified by in situ hybridization and thus remain uncharacterized. One such transcript encodes the protein neuronatin. Neuronatin has been shown to regulate calcium levels in non-neuronal cells such as pancreatic or embryonic stem cells, but its function in mature neurons remains un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 81 publications
3
48
0
Order By: Relevance
“…It is interesting that NNAT was not detected in dendrites of other retinal neurons, as it has been observed in hippocampal neurons (Oyang et al, 2011). The only exception of altered NNAT intracellular localization was detected in RHO knockout retinas at P15.…”
Section: Resultsmentioning
confidence: 67%
“…It is interesting that NNAT was not detected in dendrites of other retinal neurons, as it has been observed in hippocampal neurons (Oyang et al, 2011). The only exception of altered NNAT intracellular localization was detected in RHO knockout retinas at P15.…”
Section: Resultsmentioning
confidence: 67%
“…Accordingly, it has been recently reported that Nnat mRNA is translated in hippocampal dendrites in response to blockade of action potentials and NMDA-receptor-dependent synaptic transmission and can adjust dendritic calcium levels by regulating intracellular calcium storage. 34 Authors thus proposed that neuronatin may impact synaptic plasticity by modulating dendritic calcium levels, thereby potentially regulating neuronal excitability, receptor trafficking and calcium-dependent signaling. In adult brain, Nnat is predominantly expressed in parvalbumin-positive GABAergic interneurons.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronatin has also been proposed to mediate its effects through modulation of cellular calcium flux, with consequent effects on activation of downstream signaling pathways, including extracellular signal-regulated kinase (18, 24). It has been reported that overexpression of the α-isoform resulted in phosphorylation and therefore likely increased transcriptional activation by cAMP-response element-binding protein (CREB) in adipocytes (33).…”
Section: Discussionmentioning
confidence: 99%
“…Neuronatin mRNA can be spliced into two variants, generating proteins of 81 (α) and 54 (β) amino acids in length (4, 13). Both variants are predicted to possess a single transmembrane domain and seem to reside in the endoplasmic reticulum (ER) in neurons (12, 18, 24). Neuronatin-α is the isoform preferentially reduced in the β-cells of diabetic rodents (1, 12).…”
mentioning
confidence: 99%